Making better use of skills and migration in Poland - Brandt, Nicola (Paris, 2016)
"To continue catching up with living standards in other OECD countries Poland needs to invest in higher skills. Crucial elements include: i) making sure that all children have access to high-quality early childhood education; ii) strengthening the basic skills of vocational education students and the relevance of their studies through stronger links with firms; and iii) improving the quality of universities by linking university teachers’ pay and career progress with their teaching and research performance. The Polish government has taken action in many of these areas. More needs to be done to put immigrants’ skills to better use. Polish return migrants frequently complain about difficulties in using their skills acquired abroad, while many immigrants of foreign origin work in professions that do not match their qualifications. Ongoing reforms to improve recognition of foreign credentials and new possibilities to validate work experience through formal qualifications will be helpful."